Pakistan's Foreign Policy : A Reappraisal - Amin, Shahid M. (Karachi Oxford University Press, 2010)
"This book is a penetrating analysis of Pakistan's foreign policy from the time of Independence in 1947 until the beginning of the new millennium." "The formulation of Pakistan's foreign policy has been discussed from a fresh perspective. The author has tried to pragmatically examine the structural failures of Pakistan's foreign policy-making process and calls for new thinking on various aspects of Pakistan's foreign policy, with special emphasis on Pakistan-India relations vis-ci-vis Kashmir, and suggests various policy options and indicates their possible consequences for Pakistan. The author makes a strong plea for realism and moderation, taking into account the best interests of Pakistan, particularly in view of the acquisition of nuclear weapons by both India and Pakistan." "The book is based on the author's personal observations and analysis during thirty-nine years of diplomatic service as Pakistan's Ambassador and Special Envoy to various countries around the world." "This new edition contains a chapter on the post 9/11 developments in Pakistan's foreign policy."--Jacket.
Include Index
Previously published: 2000.
Keywords: Pakistan -- Diplomatic relations -- Politics and government